54=6(y-87)

Simple and best practice solution for 54=6(y-87) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 54=6(y-87) equation:



54=6(y-87)
We move all terms to the left:
54-(6(y-87))=0
We calculate terms in parentheses: -(6(y-87)), so:
6(y-87)
We multiply parentheses
6y-522
Back to the equation:
-(6y-522)
We get rid of parentheses
-6y+522+54=0
We add all the numbers together, and all the variables
-6y+576=0
We move all terms containing y to the left, all other terms to the right
-6y=-576
y=-576/-6
y=+96

See similar equations:

| 7x+3=6-2x | | 2(x+4)=3x+24 | | 180=6x+180 | | 192.95=(x+6.70+4.20) | | 9w-8w=18 | | (6+y)(-4+y)=0 | | 7x+8(x=9) | | 5x-40=9x+16 | | 5x+3-2x=7x+2-3 | | 2=k-71/8 | | 2x+3x-5=45 | | 2x^2+2x-61=0 | | 19x+19x-2x=14 | | 7(t+6)=63 | | (20z-10)=15 | | 5.7(x-2)=0.3+18.6 | | X-1=-1x-9 | | 2x+20=10x+4 | | 3198=39(p+25) | | 2/5h+1/5h=18/5 | | 2(10)=35x | | 9w+8w-16w-16w=17 | | -19-r=-14 | | 5.7(x-2)=0.3x18.6 | | 12/13=x/7 | | 7y+3=8y-7+6y | | -4(w+2)=16 | | 3198=25(p+39) | | 5(s-76)=20 | | -4(x-1)=-5+7x | | F(-3)=12/2x+1 | | 4v-5v-16v+13v-9v=19 |

Equations solver categories